The influence of fixed peer tutoring on student academic achievement: An experience in primary school mathematics - Andrés Martí-Alcaide, Francisco Alegre, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years it has been observed that mathematics is the subject with the lowest results in Spain and Europe. Several authors indicate that this low performance is due, among other factors, to a traditional teaching approach. In this experiment, an experience of peer tutoring in the area of mathematics was carried out in a 1st grade classroom. The number of participants was 18, forming 9 pairs of students. A pretest-posttest quasi-experimental design was used with no control group. The effect of this methodology on students' academic performance was analyzed. The analysis of the results showed an overall statistically significant improvement in academic performance (t-test =3.11, p<.01). The effect size associated with the experience was Hedge's g = 0.51. Despite the success of this experience, these results should be viewed with caution. The fact that this was an experience of short duration, with a small number of students and the absence of a control group should lead the reader to consider the final results of this work cautiously.